Aspectos Procesales del Amparo - Viera Arévalo, Rafael (2014)
In this article the author seeks to address the general amparoprocess under Peruvian law, according to their legislation, jurisprudence and doctrine. Also he analyzed the object of protection of amparo, and the current situation which is facing due to its denaturation by its indiscriminate use. that situation is consider by our current Constitutional Procedural Code, which states the exceptional nature of this resource to address violations of fundamental rights, so that evaluation of their origin must be on a case by case basis. Finally, the author analyzes the special status of the precautionary measures within an amparo process.